Harry Sue - Stauffacher, Sue (Knopf, 2005)
Although tough-talking Harry Sue would like to start a life of crime in order to be "sent up" and find her incarcerated mother, she must first protect the children at her neglectful grandmother's home day care center and befriend a paralyzed boy.